The relationship between fearing of school with the psychological and social adoption to pupils of the third primary classes - saade, Essam (Journal of Physical Education, 2014)
The first experience of entering school is very important to the child ,many studies found that the children who failed in getting school were facing the failure of studying in the future , as well as the difficulties of social is rationing comparison with their partners ,the research problems of the problems of the pupils aren't being diagnosed that may cause increasing of these problems and its reflections on the studying level as well as the neglecting of the psychological sied of the child ,by getting some joys and happiness to his life all these facts increasing the fears of children from school ,the goals dealing with the knowing the knowing the level of the psychological and social adoption with the level of fearing from school ,beside knowing the relationship between the psychological and social adoption with the reducing of fearing from school , where as the premise of the reseated says that there is allow level of social and psychological adaptation while there is a high level of fearing of from school , this experiment done or as ample of the third primary classes pupils ,the theory in clouded the fear as pacts and its kinds and the psychological and the social ,the last study loses the attributive curriculum on a sample of the third classes pupils about (45) pupils it shows , the fourth level the researcher used the stathestics bag (spss) for treating data, the discussion done depending on the scientific researches ,the fifth part handle the alow level of there is a low level of the psychological and social adoption and the equarelant of the fear level ,the researcher recommended the using of psychological criteria always and it's important to make a conversation meeting among teachers as well as activating the rule of the educational guide in the primary school